2006
DOI: 10.1088/0305-4470/39/5/003
|View full text |Cite
|
Sign up to set email alerts
|

Exact diagonalization of the XY-Hamiltonian of open linear chains with periodic coupling constants and its application

Abstract: A new method of diagonalisation of the XY-Hamiltonian of inhomogeneous open linear chains with periodic (in space) changing Larmor frequencies and coupling constants is developed. As an example of application, multiple quantum dynamics of an inhomogeneous chain consisting of 1001 spins is investigated. Intensities of multiple quantum coherences are calculated for arbitrary inhomogeneous chains in the approximation of the next nearest interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…[34], the analytical expressions are complicated. For this reason, we will employ the numerical calculation to investigate whether the Lyapunov control is suited to the case for the period l > 3.…”
Section: Scalability and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[34], the analytical expressions are complicated. For this reason, we will employ the numerical calculation to investigate whether the Lyapunov control is suited to the case for the period l > 3.…”
Section: Scalability and Discussionmentioning
confidence: 99%
“…Finally, we have shown that replacing the fast time-varying control fields with square wave pulses are possible, which simplifies the experimental realization. [34,36,37]. When l = 3 and d = 2, the matrix reads, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physics behind the above result, is that as the distance between the weakened bonds becomes larger, then lower values of J are required to produce the same effect and, in the limit of very large n then J c approaches 0 which indicates that it effectively requires cutting the chain in order to produce the same result. The analytical treatment and proof of this relation is beyond the scope of the present work and will be presented elsewhere as it involves the non-trivial diagonalisation of a chain of n spins with periodically modulated couplings and periodic boundary conditions 27 . The case of a single site with transverse field in an n-periodic chain has been investigated analytically, e.g., in Ref.…”
Section: E Generalization To N-site Periodmentioning
confidence: 99%
“…In this paper we will consider the anisotropic XY-model in a transverse field on the inhomogeneous periodic (closed) chain consisting of N cells composed of n sites, whose version on the open chain has been recently addressed by Feldman [9]. It has also been studied by Tong and Zhong [10] and Derzhko et al [11], who have restricted their analysis to the study of the thermodynamic properties.…”
Section: Introductionmentioning
confidence: 99%